PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Erma Tria Oktaviani; Erna Puspita; Badrus Zaman (Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study is to analyze the effect of company size partially on dividend policy; analyze the effect of profitability partially on dividend policy; analyze the effect of liquidity partially on dividend policy; analyze the effect of company size, profitability and liquidity simultaneously on dividend policy in companies food and beverages listed on the Indonesia Stock Exchange in 2018-2021. This study used a type of associative research. Associative research is research used to see the relationship between variables in the population. This study examines the effect of company size, profitability, liquidity on dividend policy in food and beverage companies listed on the IDX in 2018-2021. The result of this study is the result of the t test obtained the variable probability value of company size obtained a significant level of 0.010 it can be said that Ln has a significant effect on dividend policy. The results of hypothesis testing (H2) prove that there is an influence between profitability and DPR. From the results of the t test, the ROA value obtained a significant level of 0.031<0.05. The results of hypothesis testing (H3) prove that there is no influence between CR and DPR. From the results of the t test, the CR value is greater than the significant level, which is 0.949>0.05. Based on the f test that has been done, sig. <0.05 with a value of 0.022< 0.05 reflects that together (simultaneously) Ln, ROA and CR on dividend policy.